Cellulolytic Bacteria Isolation from Sugarcane Garden Soil - Arief Muammar; Mesha Arjuna; Maria Manullang; Endah Retnaningrum (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
The soil surrounding the sugar cane garden is a promising habitat for cellulolytic bacteria because it contains a source of cellulose, hemicellulose, and other carbon sources derived from the sugar canes remaining organic matter.  This study attempts to determine the presence of cellulolytic bacteria isolated from sugar cane garden soil, as well as the ability of cellulolytic bacteria to degrade cellulose based on optical density and sugar reduction values isolated from sugarcane garden soil.  We collected soil samples from five points (T1, T2, T3, T4, T5), isolating the bacteria in CMC (Carboxyl Methyl Cellulose) medium, qualitatively testing the cellulase enzyme activity with Congo Red and Iodine Assays, and quantitatively using the DNS Assay. The results of the qualitative test with the Congo Red assay revealed that there were three positive isolates with a clearly visible clear zone, namely TII C4, TII C1, and TIV C4, and after quantitative supernatant tests, the OD values of all isolates were higher than the negative control in supernatant samples using 540nm wave length using spectrophotometer, by using synthetic cellulose called Carboxy Methyl cellulase (CMC) as a substrate in the cellulase enzyme test.